2020
DOI: 10.1177/1477370820932080
|View full text |Cite
|
Sign up to set email alerts
|

Planned hooligan fights: Contributing factors and significance for individuals who take part

Abstract: Several European countries have recently been confronted with mutually arranged confrontations between hooligan groups in a predesignated setting. This article explores the significance of this form of collective violence for those involved and how this relates to existing collective violence theory. In addition to international and national questionnaires and subsequent in-depth interviews with police officials, two case studies were conducted and compared with a ‘regular’ (not mutually arranged) hooligan con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Observational studies have shown that enforcement by authorities that is seen as too strict or unjust, could lead to more aggressive of unwanted behavior (e.g. Stott & Adang, 2003). This could also be the case when it comes to fireworks, since supporters often reported that they felt that professionals did not understand or appreciate them, consciously tried to thwart them, or even wanted or tried to ban them from the stadium all together.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have shown that enforcement by authorities that is seen as too strict or unjust, could lead to more aggressive of unwanted behavior (e.g. Stott & Adang, 2003). This could also be the case when it comes to fireworks, since supporters often reported that they felt that professionals did not understand or appreciate them, consciously tried to thwart them, or even wanted or tried to ban them from the stadium all together.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the three head clubs has more the one organized fan base. The crowd violence is ignited to different proportions with different opponents or specific seasons [ 2 , 6 , 10 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The research by van Ham et al [ 2 ] aims to improve the understanding of the extent to which mutually organized clashes differ from ‘regular’ clashes between fans, seeking to fit this with existing theories of violence in football. Data were collected from different sources through questionnaires, interviews, case studies, comparison of cases, and analysis of offenders, identifying behavioral indicators exploring the existence of significant differences in the relationship between violent acts in sports and measures of psychological traits using t and chi-square tests.…”
Section: Sports Spectators’ Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Countries have been confronted with crime and violence committed by various types of criminal groups, varying from (juvenile) street gangs to hooligan firms, and from outlaw motorcycle gangs (OMCGs) to mafia-type organizations (Barker 2018;Bjørgo 2019;Kazyrytski 2017;Klein et al 2006;Paoli 2003;Van Ham et al 2020;Varese 2020). Countries use very different judicial approaches to membership and crimes committed by such groups.…”
Section: Introductionmentioning
confidence: 99%